Disruption of Claudin-1 Expression by miRNA-182 Alters the Susceptibility to Viral Infectivity in HCV Cell Models - Riad, Sarah E.; Elhelw, Dalia S.; Shawer, Heba; El-Ekiaby, Nada; Salah, Ayman; Zekri, Abdelrahman; Esmat, Gamal; Amleh, Asma; Abdelaziz, Ahmed I. (Frontiers in Genetics, 2018)
HCV entry involves a complex interplay between viral and host molecules. During post-binding interactions, the viral E2 complexes with CD81 receptor for delivery to the tight junction proteins CLDN1 and OCLN, which aid in viral internalization. Targeting HCV entry receptors represents an appealing approach to inhibit viral infectivity. This study aimed at investigating the impact of targeting CLDN1 by microRNAs on HCV infectivity. miR-155 was previously shown to target the 3’UTR of CLDN1 mRNA. Therefore, miR-155 was used as a control in this study. In-silico analysis and luciferase reporter assay were utilized to identify potential targeting miRNAs. The impact of the identified miRNAs on CLDN1 mRNA and protein expression was examined by qRT-PCR, indirect immunofluorescence and western blotting, respectively. The role of the selected miRNAs on HCV infectivity was assessed by measuring the viral load following the ectopic expression of the selected miRNAs. miR-182 was identified in-silico and by experimental validation to target CLDN1. Both miR-155 and miR-182 inhibited CLDN1 mRNA and protein expression in infected Huh7 cells. Ectopic expression of miR-155 increased, while miR-182 reduced the viral load. In conclusion, despite repressing CLDN1, the impact of miR-155 and miR-182 on HCV infectivity is contradictory. Ectopic miR-182 expression is suggested as an upstream regulator of the entry factor CLDN1, harnessing HCV infection.